2020
DOI: 10.3390/ijms21103654
|View full text |Cite
|
Sign up to set email alerts
|

Differential ESR1 Promoter Methylation in the Peripheral Blood—Findings from the Women 40+ Healthy Aging Study

Abstract: Background Estrogen receptor α (ERα) contributes to maintaining biological processes preserving health during aging. DNA methylation changes of ERα gene (ESR1) were established as playing a direct role in the regulation of ERα levels. In this study, we hypothesized decreased DNA methylation of ESR1 associated with postmenopause, lower estradiol (E2) levels, and increased age among healthy middle-aged and older women. Methods We assessed DNA methylation of ESR1 promoter region from dried blood spots (DBSs) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 82 publications
1
5
0
1
Order By: Relevance
“…Our results suggested that methylation of this novel island depends on ER but not on the estrogen binding. As previously reported, methylation of ESR1 in proximal regulatory regions was not associated with estradiol levels [ 30 , 31 ]. Since the 151-bp island is in a proximal promoter, its degree of methylation might not be associated with estradiol levels.…”
Section: Discussionsupporting
confidence: 64%
“…Our results suggested that methylation of this novel island depends on ER but not on the estrogen binding. As previously reported, methylation of ESR1 in proximal regulatory regions was not associated with estradiol levels [ 30 , 31 ]. Since the 151-bp island is in a proximal promoter, its degree of methylation might not be associated with estradiol levels.…”
Section: Discussionsupporting
confidence: 64%
“…For this purpose, we aim to investigate the estrogen receptor genes (ER1, ER2, GPER), the glucocorticoid receptor (NR3C1) as well as the serotonin transporter (5-HTTLPR) and the respective relationships with a resilient menopausal transition or the development of depression in the perimenopause. For example, a recent study by our workgroup found a positive relationship between the methylation of the ERα enhancer and depressed mood in women around the menopause [67]. Consequently, one goal is to investigate the autoregulation between estradiol and the estrogen receptor genes with regard to methylation patterns and subsequent effects on the participants' mood.…”
Section: Introductionmentioning
confidence: 99%
“…[76][77][78] Using the online tool provided by Hannon et al (2015), 76 we found that methylation of CpGs located in the assessed DNA region of ESR1 was strongly correlated between blood and brain in the same individuals. 35 Therefore, methylation variations in blood may reflect methylation variations in the brain, for the assessed CpGs of ESR1.…”
Section: Discussionmentioning
confidence: 99%
“…Women who took part in this study were recruited in the context of a larger investigation, the "Women 40+ Healthy Aging Study". [33][34][35][36] Women were recruited using flyers, social media (eg: Facebook), and journal articles. The prospective participants completed an online selfscreening to verify their eligibility for the study.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation